The Strategy of Joko Widodo’s Political Communication on 2019 Election Winning in Papua - Abdurrahman, Abdurrahman; Ruchianderan, Riffal; Samputra, Palupi Lindiasari (Journal of Strategic and Global Studies, 2021)
The purpose of this research is to (1) analyze the influence of trans papua, noken and cultural approach to Jokowi's victory in Papua, both partially and simultaneously, (2) analyze Jokowi's winning strategy in Papua. The research method uses a quantitative approach with cross-sectional data as many as 29 districts in the 2019 general election. Data analysis uses multiple linear regression, with the Jokowi winning vote variable as the dependent variable, noken, trans papua voter characteristics and culture as an independent variable. The results showed that there was a positive and significant influence of the Noken system in Papua on Jokowi's victory. On the contrary, there is no statistically significant effect between trans Papua and cultural approaches to Jokowi's victory. But all three should be considered as Jokowi's winning strategy in Papua, because based on the F-test there is a significant relationship of the three variables. An effective priority strategy to increase voter votes for the Jokowi-ma'ruf pair is through a noken approach or utilizing traditional leaders.